The mediating role of self-efficacy in the relationship between past professional training and burnout resilience in medical education: a multicentre cross-sectional study - Erschens, Rebecca; Schröpel, Carla; Herrmann-Werner, Anne; Junne, Florian; Listunova, Lena; Heinzmann, Andrea; Keis, Oliver; Schüttpelz-Brauns, Katrin; Herpertz, Sabine; Kunz, Kevin; Zipfel, Stephan; Festl-Wietek, Teresa (BMC medical education, 2024)
Meta-analyses indicate a high prevalence of burnout among medical students. Although studies have investigated different coping strategies and health interventions to prevent burnout, professional experience’s influence on burnout resilience as seldom been explored. Therefore, in our study we aimed to examine the self-efficacy’s mediating role in the relationship between past vocational training and burnout resilience. In the process, we also analysed the associations between study-related variables and burnout resilience. In our cross-sectional study, we analysed the data of 2217 medical students at different stages of their university education (i.e. 1st, 3rd, 6th, 10th semester, and final year) at five medical faculties in Germany. The questionnaire included items addressing variables related to medical school, previous professional and academic qualifications, and validated instruments for measuring burnout and self-efficacy. The overall prevalence of burnout was 19.7%, as defined by high scores for emotional exhaustion and notable values in at least one of the other two dimensions (cynicism or academic efficacy). Higher levels for self-efficacy (p < .001), having children (p = .004), and financing education with personal earnings (p = .03) were positively associated with burnout resilience, whereas having education financed by a partner or spouse (p = .04) had a negative association. In a mediation analysis, self-efficacy exerted a suppressor effect on the relationship between vocational training and burnout resilience (indirect effect = 0.11, 95% CI [0.04, 0.19]). Self-efficacy’s suppressor effect suggests that the positive association between vocational training and burnout resilience identified in the mediation analysis disappears for students who have completed vocational training but do not feel efficacious. Those and other findings provide important insights into the psychological mechanisms underlying the development of burnout resilience in medical students and suggest the promotion of self-efficacy in medical education.
Gesehen am 18.02.2025